1969
DOI: 10.12669/pjms.306.5433
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-social correlates of hypertension disease

Abstract: Background and Objective : Research evidence supports the relationship of psychological and demographic factors with hypertension and these variables are strongest predictors of hypertension which are scarcely studied in Pakistan. The present study was carried out to explore the correlation of depression, anxiety, stress and demographic factors with hypertension. Method: We used correlation research design and a sample of (N = 237), hypertensive patients (N = 137) and their age matched healthy controls (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Another study [ 46 ] used a cut-off value of BP ≥ 160/90 mm Hg for children aged 5–10 years and BP ≥ 165/90 mm Hg for adults aged 20–60 years. Four studies enrolled previously diagnosed cases of hypertension without specifying the standard methods used for diagnoses [ 32 35 ] ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study [ 46 ] used a cut-off value of BP ≥ 160/90 mm Hg for children aged 5–10 years and BP ≥ 165/90 mm Hg for adults aged 20–60 years. Four studies enrolled previously diagnosed cases of hypertension without specifying the standard methods used for diagnoses [ 32 35 ] ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The level of psychological well-being has an impact on the risk of the developing hypertension, which was confirmed by scientific studies [40,41]. Health professionals confirm a significant cross-correlation between hypertension and depressive disorders [20]. Consequently, a higher level of psychological resistance to the various conflict situations of elderly women with hypertension can be explained by a direct relationship between the state of health of these patients in stressful conflict situations and a calm state.…”
Section: Discussionmentioning
confidence: 72%
“…It is known that interpersonal conflicts are the most common types of chronic stress [17], which in its turn leads to the development of hypertensive diseases [18,19]. Scientists believe that stress is an important factor in the development of hypertension due to the fact that the heart rate is significantly increased under stress conditions [20]. Eventually, various stress and depression states are barriers to the treatment of hypertension in patients of varying gender and age [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the concept of stress had been studied for a long time (3)(4)(5), the relationship between stress and other variables had also been investigated. In this study, self esteem (105)(106)(107), anxiety (108)(109)(110), and depression (111)(112)(113)(114)(115) were chosen as the most investigated variables. For criterion-related validity, it was observed that the scale had the expected relationship between the related variables.…”
Section: Discussionmentioning
confidence: 99%